An overview of experimental techniques of the investigation of water-diesel emulsion characteristics droplets micro-explosion - Ismael, M.A. (Asian Research Publishing Network, 2016)
Emulsified fuels considered as a promising alternative fuel that could solve and meet the increasingly stringent emission regulations for diesel engines due to their capability of reduction the harmful exhaust emission, such as carbon monoxide (CO), nitrogen oxides (NOx) and particulate matter (PM). The admission of water into the diesel fuel has significant advantages. One of these advantages is the possibility of occurrence of the so-called micro-explosion phenomena. There is a number of experimental techniques and visualization systems to investigate and analyse the uses of the water-diesel (W/D) emulsion fuel, especially regarding micro-explosion phenomena. Micro-explosion is the rapid breakup of fuel droplets and hence burst into smaller droplets which enhance fuel evaporation and hence improving the air-fuel mixing process. An investigation of micro-explosion of the smaller droplets is important. This review paper discussing the advantages of using the emulsion fuel and the different experimental techniques used to detect the micro-explosion phenomena in addition to the factors affecting the onset of micro-explosion processes and proposes potential research areas for W/D emulsion fuel studies. Most of the studies in the literature agree that W/D does result in a reduction in NOx and PM exhaust gas emissions. There is, however, some inconsistencies of the experimental techniques with respect to the heating process which affects the onset and the strength of the micro-explosion process. The factors that affect the microexplosion phenomena consist of different parameters such as the distribution of the water in the emulsion, the size of the emulsion droplet, type and percentage of the surfactant, ambient temperature and pressure. Â©2006-2016 Asian Research Publishing Network (ARPN).